Pengaruh teknik pengemasan dan jenis kemasan terhadap mutu dan daya simpan ikan pindang bumbu kuning - Imam Budi Mulyawan; Baiq Rien Handayani; Bambang Dipokusumo; Wiharyani Werdiningsih; Astri Iga Siska (Jurnal Pengolahan Hasil Perikanan Indonesia, 2019)
Yellow seasoned pindang fish is one of East Lombok special pindang products made of tamarind and turmeric, yet their shelf life is short. The aim of this research was to determine the effect of technique and types of packaging on the quality and shelf-life of yellow seasoned pindang fish. The method used was experimental method with completely randomized block design of 2 factors: packaging technique (vacuum and non vacuum) and packaging types (Polyprophylene (PP), Polyethylene (PE), and Alumunium Polyprophylene (Al-PP). Parameters observed were chemical (pH and water content), physical (value of L and 0Hue), microbial (total microbes and fungi) and shelf-life (fungi, gas formation and color change). The results showed that the technique and packaging types had a significant effect on the pH of the pindang at the 7th day.Packaging technique affected pH and L value at 7th and 14th day, while the moisture content and 0Hue differed markedly only on the 7th day. Packing types affected the pH at 7th and 14th. Vacuum packaging with Polyprophylene (PP) resulted in the lowest total microbials during storage, while the total fungus in all treatments were undetectable. Combination of vacuum packing with PP is recommended as the best treatment to produce yellow seasoned pindang fish, maintaining pH and moisture, preventing growth of fungi and microbes, as well as extending the shelf life up to the 7th day at ambient storage.